2016
DOI: 10.1073/pnas.1610800113
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and neuroanatomy of the clonal raider ant implicate an expanded clade of odorant receptors in chemical communication

Abstract: A major aim of sociogenomic research is to uncover common principles in the molecular evolution of sociality. This endeavor has been hampered by the small number of specific genes currently known to function in social behavior. Here we provide several lines of evidence suggesting that ants have evolved a large and novel clade of odorant receptor (OR) genes to perceive hydrocarbonbased pheromones, arguably the most important signals in ant communication. This genomic expansion is also mirrored in the ant brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
182
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(205 citation statements)
references
References 67 publications
10
182
0
Order By: Relevance
“…Nevertheless, this broader analysis further supports and indeed extends our observation that HsOR-mediated responses to hydrocarbons are not, as previously hypothesized (8,9,14), restricted to the nine-exon HsOr gene subfamily. Furthermore, within the subset of statistically significant responses, we discovered a strong bias toward the longer chain alkanes commonly found in H. saltator CHCs (5, 18).…”
Section: Responses To Cuticular Hydrocarbons In Single-sensillum Drossupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, this broader analysis further supports and indeed extends our observation that HsOR-mediated responses to hydrocarbons are not, as previously hypothesized (8,9,14), restricted to the nine-exon HsOr gene subfamily. Furthermore, within the subset of statistically significant responses, we discovered a strong bias toward the longer chain alkanes commonly found in H. saltator CHCs (5, 18).…”
Section: Responses To Cuticular Hydrocarbons In Single-sensillum Drossupporting
confidence: 89%
“…Previous work has strongly implicated the nine-exon subfamily of ORs, which makes up nearly 30% of the 347 putative Or genes in H. saltator genome (HsOrs) and is highly expanded within the ant lineage (8,9), in the detection of CHCs, based on their enrichment along the hydrocarbon-sensitive ventral portion of the worker antennae (14). Transgenic expression of a subset of these genes in Drosophila olfactory sensilla confers receptor-specific responses to a panel of CHCs.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila , pheromone receptors have been identified that belong to multiple insect chemosensory receptor families, including odorant receptors (ORs), gustatory receptors (GRs), ionotropic receptors (IRs), and pickpocket channels (PPKs) (Kohl et al, 2015). Ants have numbers of GRs, IRs, and PPKs that are typical for insects, while their OR repertoire is highly expanded (McKenzie et al, 2016; Oxley et al, 2014; Smith et al, 2011a, 2011b; Zhou et al, 2012) (Figure 1A and Table S1). This raises the possibility that the expansion of ORs specifically, rather than chemoreceptors in general, may underlie the evolution of complex chemical communication in ants.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the possibility that the expansion of ORs specifically, rather than chemoreceptors in general, may underlie the evolution of complex chemical communication in ants. Ants also have exceedingly large numbers of glomeruli in their antennal lobes, which likely mirror their expanded OR gene repertoire (McKenzie et al, 2016; Zube et al, 2008) (Table S1). Insect ORs function as chemosensory receptors by dimerizing with the highly-conserved co-receptor protein Orco to form ligand-gated ion channels (Jones et al, 2005; Larsson et al, 2004; Sato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%